The reformatting of archival documents in the Brazilian legal context: an analysis of the regulatory instruments - Filgueiras, André Luiz Caetano; de Albite Silva, Sérgio Conde; Lousada, Mariana [UNESP] (My University, 2021)
This article discusses the reformatting of documents in the Brazilian legal context. They have been analyzed from the microfilming law to the latest draft legislation on digitization. It highlights that digitization advances in public institutions without being in line with a document management program for these digital surrogates that do not meet the requirements for authenticity assurance.
El reformateo de documentos de archivo en el contexto legal brasileño: un análisis de los instrumentos reguladores
A reformatação de documentos arquivísticos no contexto legal brasileiro Uma análise dos instrumentos regulamentadores
Keywords: digitization; microfilming; reformatting of documents